O agronegócio da soja brasileira e a sua internacionalização na ordem econômica global, entre 1990 e 2018 - Corte, Tiago Dalla (2019)
The theme of this research is the insertion of Brazilian soybean agribusiness into the global economic order. In order to delimit the approach of this object of investigation, its study focuses on factors that determined it: the acceleration of the globalization process, the rise of the neoliberal discourse, the end of the state protagonism as agribusiness developer agent in Brazil, the Westernization of the food diet, the reduction of protectionist policies, the rise in international agricultural prices, strong Chinese economic growth and the formation of a financial bubble in China. In this context, the thesis proposes to examine, through the method of historical approach and its dialogue of sources, as well as from a macro perspective, historical-economic processes that have led Brazilian soybean agribusiness to become one of the fundamental pillars for the maintenance of the global economic order in force at the beginning of the 21st century. To that end, the specific objectives of this thesis are: the understanding of the historical evolution of soybean cultivation in Brazil and the development of its productive chains; to review the state promotion of Brazilian soybean agribusiness from 1970 to 1990 and to understand the new agricultural policy and the international redirection of Brazilian soybean agribusiness in the 1990s; to describe the cycle of internationalization of Brazilian soybean agribusiness from the 2000s; evidence the global consolidation of Brazilian soybean agribusiness based on Brazil's fiscal crisis in the years 2014-2016 and the financial bubble inflated by the reduction in US interest rates as well as the increase in Chinese debt from 2008. Given the methodological structure exposed , it is the problem to be answered in this paper: how did the expansion take place, what are its determinants and what is the historical economic role of the global insertion of Brazilian soybean agribusiness in the beginning of the 21st century? As a hypothesis to be tested, it is understood that there was a global insertion of Brazilian soybean agribusiness in an unplanned manner, as demonstrated by the lack of investments in infrastructure, which generated a series of bottlenecks (such as the difficulty of access to markets due to of high transport costs) that limited the process, but which, however, did not prevent Brazilian soy from ascending to a strategic resource role. This thesis shows that the globalization of soybean agribusiness was essential for accelerating the growth of the world economy, identifying that the credit expansion of the Chinese economy was the determining factor for the development of Brazilian soybean agribusiness, making it the most dynamic sector of the national economy. In this sense, it is exposed that the global realignment of the Brazilian soybean agribusiness sector does not correspond to a transitory phenomenon, but represents a structural change of historical importance for the Brazilian economy.